Distribution of methane enrichment zone in abandoned coal mine and methane drainage by surface vertical boreholes: A case study from China - Feng, G.; Hu, S.; Li, Z.; Jiang, H.; Zhang, Y.; Xu, Guang; Wang, Z.; Kang, L. (ELSEVIER, 2016)
Many abandoned mines with small gobs were produced by the old mining method in China. These gobs with different widths contain a considerable amount of methane. In this paper, FLAC3D software is used to investigate the rock mass stress distributions. Based on the stress distribution results, the methane enrichment zones (MEZ) are identified in different gobs with various widths ranging from 30 m to 180 m. The results show that the MEZ of these gobs consistently exhibit a “crab shell” shape, and the range of the MEZ in the roof of each gob is larger than that in the floor. The ranges of the MEZ increase as gob widths grow; however, the gob widths have limited impact on the ranges of the MEZ in coal pillars close to gobs. The ranges of the upper and lower boundaries of the MEZ both increase as gob widths increase, and they decrease as the distance from the middle of gobs increases. The gas can flow freely in the MEZ of gobs, and once the MEZ of a gob is extracted, the methane in the MEZ of adjacent gobs flows into that gob. Based on these results, a method is proposed and first applied to an abandoned coal mine in China by drilling surface vertical boreholes into the upper part of the MEZ of gobs.A low negative pressure of approximately −3 kPa is used for gob methane drainage. The methane in the MEZ where the borehole is located flows rapidly into the borehole at first, with a peak gas flow rate of 6.4 m3/min. Then, as the methane in this MEZ is exhausted and the methane in the MEZ of adjacent gobs fails to quickly resupply the first MEZ, the flow rate begins to decline sharply. Finally, the methane from the MEZ of adjacent gobs around the borehole flows slowly through the coal pillars. Thus, the flow rate in the borehole is stabilized at approximately 2.5 m3/min. The overall average flow rate reaches 3.5 m3/min, and the whole borehole methane extraction period lasts more than 346 days. The methane concentration is generally more than 80% and remains relatively stable.